Kemiskinan Pedesaan dan Angka Partisipasi Sekolah di Indonesia - Rofi'i, Yulianto Umar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study analyzes the influence of rural poverty on school enrollment rates in Indonesia. Using time series data for the period 1998-2021, the analysis model used is simple linear regression. The study revealed that school enrollment rates and rural poverty levels in Indonesia fluctuate throughout the year. The estimation results indicate that rural poverty has a negative effect on school enrollment rates at both elementary school, middle school and high school levels. Therefore, efforts to increase school participation in Indonesia must be in line with efforts to reduce rural poverty levels.